Effect of Additional Dried Tubifex sp. in Commercial Feed Against Color Intensity of Guppy (Poecilia reticulata) - Nurjihan, Haniah Istiqomah; Kasprijo, Kasprijo; Muslih, Muslih; Soedibya, Petrus Hary Tjahja; Fitriadi, Ren; Esa, Yuzine (Department of Aquaculture, 2024)
Guppy fish (Poecilia reticulata) is a type of ornamental fish that is in great demand, because of its small size and beautiful color. The color of ornamental fish will generally fade, due to a lack of carotenoids in their feed. The purpose of this study was to determine the effect of giving Tubifex sp. in commercial feed to increase the color intensity of guppy fish and the best dose of Tubifex sp. The test fish used were male guppy fish strain HB Red. This study used a completely randomized design (CRD) method with five treatments and three replications, that is commercial feed with the addition of Tubifex sp. with doses of 0% (P1), 2% (P2), 4% (P3), 6% (P4), and 8% (P5). Parameters observed were color intensity (chroma value), survival, and water quality. Addition of Tubifex sp. in commercial feed gave the effect with the highest yield on P5 at a dose of 8%, with an increase in color intensity (chroma value) of 4,21±0,25d. At P1 it gave an increase of 1,19±0,02a, P2 was 1,34±0,04a, P3 was 1,81±0,21b, and P4 was 2,88±0,18c. So, the best treatment is P5 (8%). Survival showed the results were not significantly different, that is 100%. Water quality is included in the tolerance limit of fish with the results of temperature 26,6 – 27,4°C, pH 7,4 – 7,9, and DO 6,2 – 7,7 mg/L.